2017
DOI: 10.1155/2017/8345704
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Localized Faults in Multistage Gearboxes: A Vibrational Approach by Means of Automatic EMD-Based Algorithm

Abstract: The gear fault diagnosis on multistage gearboxes by vibration analysis is a challenging task due to the complexity of the vibration signal. The localization of the gear fault occurring in a wheel located in the intermediate shaft can be particularly complex due to the superposition of the vibration signature of the synchronous wheels. Indeed, the gear fault detection is commonly restricted to the identification of the stage containing the faulty gear rather than the faulty gear itself. In this context, the pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The Hilbert-Huang transform (HHT) was introduced as a better methodology for analyzing non-linear and non-stationary signals [23]. This technique is now often used for rotational-machine fault diagnosis [24][25][26][27]. The HHT method uses a time adaptive operation known as empirical mode decomposition (EMD) to decompose the signal into a group of complete and orthogonal components, denoted as intrinsic mode functions (IMFs), that represent the intrinsic oscillation modes of the fault-related components of a vibration signal.…”
Section: Introductionmentioning
confidence: 99%
“…The Hilbert-Huang transform (HHT) was introduced as a better methodology for analyzing non-linear and non-stationary signals [23]. This technique is now often used for rotational-machine fault diagnosis [24][25][26][27]. The HHT method uses a time adaptive operation known as empirical mode decomposition (EMD) to decompose the signal into a group of complete and orthogonal components, denoted as intrinsic mode functions (IMFs), that represent the intrinsic oscillation modes of the fault-related components of a vibration signal.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this drawback, Wu and Huang proposed the ensemble empirical mode decomposition (EEMD) method, which is a noise-assisted data analysis method by adding finite white noise to the investigated signal [ 14 ]. Because of their ease of use and excellent performance for complex signals, EMD-based methods have been widely applied in fault diagnosis [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. For example, Lei et al applied the EEMD to the rub-impact fault diagnosis of a power generator and early rub-impact fault diagnosis of a heavy oil catalytic cracking machine [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Park et al applied EEMD to the transmission error measured by the encoders of the input and output shafts to classify the spall and crack faults of gear teeth [ 21 ]. Buzzoni et al applied EMD-based methods for the diagnosis of localized faults in multistage gearboxes, and they pointed out that EMD-based methods were particularly suitable for industrial applications since they were completely automatic [ 22 ]. Considering the nonlinearity of the signal in real hoists and the industrial ease of use, EEMD is selected in this paper.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the vibration may also impact the structure life-time, component reliability, vehicle comfort, etc. The topics regarding collecting and analyzing the vibration and noise signals at some reference points for faulty diagnosis [2][3][4], power system health monitoring [5,6], structure modal analysis [7][8][9][10][11], and noise and vibration control [12][13][14] have been popular for decades. From this literature, it is also shown that in some circumstances of faulty diagnosis and noise control, the key information contained in the vibration and noise signals are presented as some special combinations of sinusoidal signals.…”
Section: Introductionmentioning
confidence: 99%